Risk-averse pricing decisions based on prospect theory - Shaban, Ibrahim Abdelfadeel (Decision Making: Applications in Management and Engineering, 2023)
This study examines the risk behaviour of a decision-maker regarding pricing decisions with the aid of the newsvendor model. In this regard, prospect theory and reference point concept are adopted to formulate the value function of the decision-maker. Unlike the traditional reference points (quantity-based), a reference point is deemed a function of the price. It is proved that a convex combination of the maximum-expected profits and expected losses represents the reference point. Closed-form solutions for the optimum price and quantity orders are obtained under uniformly and exponentially distributed demand. Moreover, the risk when the ordering quantity does not match the actual demand is discussed. The results-based numerical experiments reveal that the risk-averse decision-maker manages to increase the price to evade different expected costs, such as shortages and overstocking. Finally, for the same risk aversion level, the maximum reduction percentage of the optimal quantity concerning the price reaches approximately 8% in the exponential distribution, whereas it decreases by approximately 30% under the uniform distribution.